The Role of PAI Learning Evaluation in Developing Adolescents' Moral Awareness in the Era of Social Media - Muhammad Syukur; Sugeng Sugeng (Lembaga Yasin AlSys, 2025)
The social media era presents complex challenges to shaping adolescent moral awareness, thereby necessitating a fundamental transformation in Islamic Education (Pendidikan Agama Islam, PAI) assessment practices. This study aims to explore the role of PAI assessment in fostering adolescents’ moral consciousness in the social media era through the perspectives of teachers as primary evaluators. Employing a qualitative phenomenological design, the research involved ten to fifteen junior and senior high school PAI teachers selected via purposive sampling. Data were collected through in-depth interviews and participatory observations and analyzed using thematic analysis with triangulation to ensure the credibility of the findings. The results reveal that PAI teachers have developed a holistic conception of evaluation that integrates cognitive, affective, and psychomotor dimensions by implementing innovative instruments such as digital portfolios, project-based evaluations, and authentic assessments through case studies. Despite challenges including students’ identity dualism, teachers’ limited digital competencies, and ethical dilemmas related to privacy, PAI assessment effectively facilitates the internalization of moral values, shapes internal moral filters, and promotes positive behavioral changes among students on social media. This study contributes theoretically to the development of an evaluation paradigm responsive to digital-age challenges and offers practical implications for enhancing the quality of character education in the contemporary era.